Letter to the editor regarding European Headache Federation guideline on the use of monoclonal antibodies acting on the calcitonin gene related peptide or its receptor for migraine prevention - Nichols, Russell; Skljarevski, Vladimir; Dell’Agnello, Grazia; Hundemer, Hans-Peter; Aurora, Sheena K. (Journal of headache and pain, 2019)
The present report provides a detailed head to head comparative study of migraine pain location at onset and during established headache between children and adults belonging to the same ethnic group. Migraine pain location in 200 children and adolescents had already been reported (Chakravarty et al. in Cephalalgia 27:1109-1114, 2007). The present report includes data collected simultaneously and in a similar fashion from 800 adult migraineurs. Significant differences have been noted in migraine pain location. Unilateral onset pain is common in adults, side locked and vertex onset pain unusual in children, holocranial onset pain much common in children and cervico-occipital onset pain much less common in children. There have been differences in evolution of migraine pain as well. During established headache unilateral pain was recorded in only a small proportion of children (10.5%) whereas it was noted in many adults' subjects (40.5%). Such a detailed comparative study had not been made earlier. [PUBLICATION ABSTRACT]